Evaluasi Lanskap Jalan Jenderal Ahmad Yani Pontianak - RULIYANSYAH, AGUS (Jurnal Arsitektur Lansekap, 2017)
ABSTRACT Streetscape Evaluation at Jenderal Ahmad Yani Street Pontianak Jenderal Ahmad Yani Street is the main street in the city of Pontianak. Ahmad Yani street landscape must be planned in order to function properly. The purpose of this study were 1) to evaluate the function of the architectural aspect, aesthetics and maintenance and 2) provide appropriate recommendations on the management of Ahmad Yani street landscape. Survey method was used in this study by dividing Ahmad Yani street down into three segments. The results showed that the segments 2 and 3 meet the criteria of architectural aspects. Aesthetic aspects for segments 2 and 3 was considered quite meet unless segment 3, while for the maintenance aspects of the three segments known that meet both criteria. Planting should be composed with the landscape tanama good to get a strong visual impression according to the social and environmental conditions of the landscape in each segment. Keywords: aesthetic, Ahmad Yani street, architectural, streetscape